2010
DOI: 10.1002/pbc.22497
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in children with sickle cell disease: A report from the Comprehensive Sickle Cell Centers Clinical Trial Consortium

Abstract: Background-Pediatric health-related quality of life (HRQOL) questionnaires have been validated in children with sickle cell disease (SCD), but small sample sizes in these studies have limited clinical comparisons. We used the baseline clinical data from the Collaborative Data (CData) Project of the Comprehensive Sickle Cell Centers (CSCC) Clinical Trial Consortium to perform a detailed, descriptive study of HRQOL using the PedsQL™ version 4.0 generic core and fatigue scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
182
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(210 citation statements)
references
References 28 publications
20
182
8
Order By: Relevance
“…Additionally, studies have shown that fatigue may reduce patients' ability to perform daily activities (13,17). Dampier et al (13,17) found that adolescents with SCD reported lower levels of sleep and rest, and elevated fatigue, compared to healthy peers; another study found that young adults with SCD reported lower levels of energy than the general population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, studies have shown that fatigue may reduce patients' ability to perform daily activities (13,17). Dampier et al (13,17) found that adolescents with SCD reported lower levels of sleep and rest, and elevated fatigue, compared to healthy peers; another study found that young adults with SCD reported lower levels of energy than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In managing serious and unpredictable complications, patients with SCD suffer numerous psychosocial problems such as reduced self-esteem, feelings of frustration (7), depression (7)(8)(9), anxiety and stress (8), and disruption of interpersonal relationships (10); these often lead to fatigue (11)(12)(13)(14) and poor quality of life (13,(15)(16)(17) in these patients. Bakri et al (10) showed that depression, anxiety and stress are prevalent in SC patients compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The SF-36 has been validated in populations with chronic diseases 29,30 and in patients experiencing chronic pain similar to SCD patients. 31 In adults with SCD, HRQoL was previously assessed using the SF-36 in large clinical studies, 12,32 and it has been validated against 2 other quality-of-life measures in SCD patients. 33 The SF-36 Health Survey consists of 36 items that cover 8 sections consisting of physical functioning; role limitations due to physical health, bodily pain, general health, vitality, and social functioning; and role limitations due to emotional problems and mental health.…”
Section: Hrqolmentioning
confidence: 99%
“…10,11 Aside from the direct physical morbidity of these recurrent painful attacks, other significant outcomes such as quality of life, school attendance, and societal participation of patients are greatly affected. [12][13][14][15][16][17][18] Moreover, high societal costs are involved. Direct costs arise from high health care utilization, and indirect costs include absence from work associated with impaired physical ability to perform daily tasks.…”
Section: Introductionmentioning
confidence: 99%